Inside the oval office : the white house tapes from fdr to clinton - Doyle, William ([S.l.] : Kodansha USA, 2002)
During the four years of research in the national archives and presidential libraries, William Doyle unearthed scores of White House tape recordings, videotapes and transcripts, many never before published. He interviewed 100 Oval Office insiders, Cabinet members, White House aides and advisers from FDR's personal secretary to Henry Kissinger. The result is a flesh-and-blood drama of the presidency in action. Presidential episodes include: Franklin D. Roosevelt - plans to detonate a sex scandal to ruin his republican opponent; Harry S. Truman - at the controls of the world's first nuclear superpower; Dwight Eisenhower - struggles with a problem he fears will wreck the USA; John F. Kennedy - on his invasion of Mississippi to crush rebellion and a massacre; Lyndon B. Johnson - when he realises he must disengage from Vietnam; Richard Nixon - crucified himself on his own tape machines; Jim Carter - as he runs a high-risk helicopter rescue of US hostages; Ronald Reagan - on conquering Grenada and plotting victory in the Cold War; Bill Clinton - tries to rescue his presidency, four years before his impeachment.